The EU services directive: Untapped potentials of trade in services - Michael Pfaffermayr; Yvonne Wolfmayr (Austrian Institute of Economic Research (WIFO), 2025)
A major step towards liberalizing the EU Internal Market for services was taken in 2006 with the EU Services Directive. This study quantifies its impact on EU trade in services and real income and identifies untapped potential due to remaining administrative barriers and weak enforcement of Single Market rules. Results are based on a structural gravity model estimated at the level of industry and country-pairs over the period 1995 to 2018. A novel country-specific indicator derived from business complaints to the EU-SOLVIT mechanism, assesses the quality of service sector reforms and remaining barriers to trade in services. Empirical estimates show heterogeneous effects across industries, with strong positive effects in publishing, IT and business services, but negative effects for some industries such as in wholesale and retail trade. On average, the Services Directive increased intra-EU trade in services by 4.4 percent, but had negligible effects on real income. If reform efforts were to match those of the strongest reformers, intra-EU export potential could increase by 6.2 percent and potential real income by 0.3 percent on average.
Keywords: F15; F16; L80; C23; C50; 330; Trade in services; European integration; Gravity model; Trade liberalization